Relationship between hair cortisol concentrations and cognitive functioning in adolescents with ADHD - Marta Llorens; Maria Barba; Jordi Torralbas-Ortega; Roser Nadal; Antonio Armario; Humberto Gagliano; Lara Urraca; Susana Pujol; Itziar Montalvo; Rebeca Gracia; Diana Polo; Laura González-Riesco; et al. (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground: Our study aimed to explore whether the hair cortisol concentration (HCC), a measure of long-term cortisol output, is associated with poorer cognitive functioning in adolescents with attention deficit and hyperactivity disorder (ADHD). We further aimed to test the potential moderating effects of sex and childhood maltreatment.Methods: In this cross-sectional study, fifty-three adolescents with ADHD were studied. The ADHD Rating Scale (ADHD-RS) and Childhood Trauma Questionnaire (CTQ) were administered. Seven cognitive tasks from the Cambridge Neuropsychological Test Automated Battery (CANTAB) were administered, and two cognitive factors (attention and memory and executive functioning) were identified by confirmatory factor analysis. A 3-cm hair sample from the posterior vertex region of the head was obtained. HCCs were determined by a high-sensitivity enzyme immunoassay kit. Multiple linear regression analyses were used to explore the association between HCCs and either cognitive performance or ADHD severity while adjusting for sex, childhood maltreatment and the ADHD-RS total score.Results: Sex moderated the relationship between HCCs and attention/memory confirmatory factor analysis (CFA) scores, with better performance in boys with higher HCCs. HCCs were not associated with executive functioning or ADHD symptoms. Childhood maltreatment was associated with inattention symptoms in adolescents with ADHD.Conclusions: Our study suggests that HCCs are positively associated with attention and memory performance in adolescents with ADHD, with a moderating effect of sex (the relationship is strongest in boys).